Pengembangan Sistem Presensi Guru UPT SMPN 34 Gresik Berbasis Web - Muhammad Ibnu Rosikhin; Farhanna Mar’i (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
UPT SMPN 34 Gresik is one of the educational institutions that faces challenges in managing teacher attendance and salaries efficiently. Because UPT SMPN 34 Gresik currently still uses manual recording of teacher attendance, so it takes quite a long time. To overcome this problem, the researcher proposes creating a web-based Teacher Attendance System using the Waterfall design methodology with a MySQL database. The aim of establishing this web-based teacher attendance system is to assist teachers in carrying out attendance attendance efficiently and assist educators and teaching staff in managing teacher salaries based on attendance better. The need for an inclusive teacher attendance system, and the need for optimal salary calculations at UPT SMPN 34 Gresik are resolved through this research. From the conclusions obtained from the process of observation, interviews and literature study, this web-based teacher attendance system is expected to increase the efficiency of human resource management in the education sector. Researchers hope to provide comprehensive and sustainable answers to the needs of UPT SMPN 34 Gresik.